2017
DOI: 10.9755/ejfa.2017.v29.i11.1500
|View full text |Cite
|
Sign up to set email alerts
|

Improvement effect of nitrogen fertilizer and plant density on wheat (Triticum aestivum L.) seed deterioration and yield

Abstract: In order to study the effect of seed deterioration, plant density and nitrogen fertilizer application on yield, yield components and somequalitative traits of wheat, a field experiment was conducted in Golestan province of Iran, as split factorial in the randomized completeblock design, with four replications in two growing seasons, 2014-2015 and 2015-2016. The experimental treatments included seedquality at 4 levels (control, 15, 30, and 45 hours of accelerated deterioration), plant density at two levels (350… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 22 publications
5
7
0
1
Order By: Relevance
“…The increase in grain yield per feddan owing to the highest seeding rate may be attributed to it gave the highest values of number of spike/m 2 (Table 3), spike length (Table 4) and number of grain/spike (Table 5) which led to raising grain yield per feddan. These results are in harmony with those of Mosanaei et al (2017), Julio et al (2017) and Masuma et al (2017).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The increase in grain yield per feddan owing to the highest seeding rate may be attributed to it gave the highest values of number of spike/m 2 (Table 3), spike length (Table 4) and number of grain/spike (Table 5) which led to raising grain yield per feddan. These results are in harmony with those of Mosanaei et al (2017), Julio et al (2017) and Masuma et al (2017).…”
Section: Resultssupporting
confidence: 91%
“…Seeding rate play an important role in the placement of seed at proper depth and stand establishment of the growing crop which ultimately affected crop growth and productivity. Mosanaei et al (2017), Julio et al . (2017) and Masuma et al .…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that N fertilization had a significant impact on all agro-physiological and yield-related traits. PH generally increased with increases in the N application rate due to elongation of the nodes in the wheat crop [40]. Differences in genetic makeup of different varieties is one of main attributes responsible for variation in PH.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that nitrogen fertilizers had a significant effect on grain yield and the 1000grain weight, and this significant increase was observed when up to 150 kg N/ha were used in traits (2). Nitrogen fertilizers have a significant effect on quantitative traits of wheat such as grains/spike, spikelets/spike, 1000-grain weight, grain yield, biological yield and harvest index (3). Plants provide carbon sources needed by the fungus and the fungus supports water and nutrients from the soil to plants.…”
Section: Introductionmentioning
confidence: 99%